Contribuições das oficinas terapêuticas de teatro na reabilitação psicossocial de usuários de um CAPS de Uberlândia-MG - Campos, Fernanda Nogueira (2005)
The latin word "officina" means a place where official people and apprenticees of some work of art produces some artifact. Inside of the mental health its practical leads for new directions, the theater workshop proposes creating an expression activities in a space that links all the arts - an unique activity of personal relations, an experience with healthy resources that stimulate the transformation, the autonomy giving alternatives of participants reintegration and also the encouraging to elaborate bad experiences in the past. This study shows the contributions of the theatre workshop in the CAPS-oeste of Uberlândia, among the analyses of the participants' discurses and criativity encenation. The theater workshop helps to create a space of communication, criation, self-discovering and self-superation, a space of subjectivity continnuous production.